Is it Possible? The Improvements of Indonesian Advocate Code of Ethics (KEAI) during the Multi Organizational - Rio Saputra; Mokhammad Najih (Varia Justicia, 2021)
The advocate profession as an officium nobile is required to carry out their duties professionally in the real terms of the implementation for the community. However, various professional advocacy organizations currently influence the effect of professionality ethical values. In this regard, it is necessary to conduct a study on how advocates' professionalism in Indonesia in accordance with the value of Pancasila as contained Law No. 18 of 2003 on Advocate (Advocate Law 2003) and Indonesian Advocates' Code of Ethics (KEAI). The research aims to harmonize KEAI and Advocate Law 2003 and create a Professional Committee for the advocate in Indonesia. This research used normative legal research with comparative and historical approaches. The result showed that the improvement of current KEAI as mandated by Advocate Law 2003 by confirming the position of the Supervisory Commission and the Honorary Council and further involving external elements, as well as elements of the state as controllers will avoid the advocate profession from the involvement of unethical behavior, slaves by the client and its involvement to the criminal offences.